Myeloid cell-derived catecholamines influence bone turnover and regeneration in mice - Kuhn, Melanie R.; Haffner-Luntzer, Melanie; Kempter, Elena; Reber, Stefan O.; Ichinose, Hiroshi; Vacher, Jean; Ignatius, Anita; Tschaffon-Müller, Miriam E. A. (Frontiers in Endocrinology, 2022)
Catecholamine signaling is known to influence bone tissue as reuptake of norepinephrine released from sympathetic nerves into bone cells declines with age leading to osteoporosis. Further, β-adrenoceptor-blockers like propranolol provoke osteoprotective effects in osteoporotic patients. However, besides systemic adrenal and sympathetic catecholamine production, it is also known that myeloid cells can synthesize catecholamines, especially under inflammatory conditions. To investigate the effects of catecholamines produced by CD11b+ myeloid cells on bone turnover and regeneration, a mouse line with specific knockout of tyrosine hydroxylase, the rate-limiting enzyme of catecholamine synthesis, in CD11b+ myeloid cells (THflox/flox/CD11b-Cre+, referred to as THCD11b-Cre) was generated. For bone phenotyping, male mice were sacrificed at eight and twelve weeks of age and harvested bones were subjected to bone length measurement, micro-computed tomography, fluorescence-activated cell sorting of the bone marrow, gene expression analysis, histology and immunohistochemistry. Support for an age-dependent influence of myeloid cell-derived catecholamines on bone homeostasis is provided by the fact that twelve-week-old, but not eight-week-old THCD11b-Cre mice, developed an osteopenic phenotype and showed increased numbers of neutrophils and T lymphocytes in the bone marrow, while CCL2, IL-6, IL-4 and IL-10 mRNA expression was reduced in sorted myeloid bone marrow cells. To investigate the influence of myeloid cell-derived catecholamines on fracture healing, mice received a diaphyseal femur osteotomy. Three days post-fracture, immunohistochemistry revealed an increased number of macrophages, neutrophils and cytotoxic T lymphocytes in the fracture hematoma of THCD11b-Cre mice. Micro-computed tomography on day 21 showed a decreased tissue mineral density, a reduced bone volume and less trabeculae in the fracture callus indicating delayed fracture healing, probably due to the increased presence of inflammatory cells in THCD11b-Cre mice. This indicates a crucial role of myeloid cell-derived catecholamines in immune cell-bone cell crosstalk and during fracture healing.